1993
DOI: 10.1002/ar.1092350303
|View full text |Cite
|
Sign up to set email alerts
|

An electron microscopic study of the harderian gland of the Syrian hamster with particular reference to the processes of formation and discharge of the secretory vacuoles

Abstract: The lipid-secreting cells of the Harderian gland of the Syrian hamster were studied using light, transmission, and scanning electron microscopy. Three morphologically different secretory cell types are identified in the gland: type I and II cells of the male gland and, distinct from either, the female gland cell. In all secretory cell types, lipid droplets in the cytoplasm were surrounded by unit membranes. Ultrastructural evidence of the involvement of the Golgi apparatus in the formation of the secretory vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…In previous studies on the HG, two or three types of glandular cells have been morphologically distinguished in various rodents: the mouse (Strum and Shear, 1982;Watanabe, 1980;Woodhouse and Rhodin, 1963), rat (Brownscheidle and Niewenhuis, 1978;Carriere, 1985;Tsutsumi et al, 1966), plain mouse (Johnston et al, 1985) and male golden hamster (Bucana and Nadakavukaren, 1973;Hoffman, 1971;Lopez et al, 1993). However, in guinea pig we distinguished four types of cells with different characteristic morphological features.…”
Section: Discussionmentioning
confidence: 76%
“…In previous studies on the HG, two or three types of glandular cells have been morphologically distinguished in various rodents: the mouse (Strum and Shear, 1982;Watanabe, 1980;Woodhouse and Rhodin, 1963), rat (Brownscheidle and Niewenhuis, 1978;Carriere, 1985;Tsutsumi et al, 1966), plain mouse (Johnston et al, 1985) and male golden hamster (Bucana and Nadakavukaren, 1973;Hoffman, 1971;Lopez et al, 1993). However, in guinea pig we distinguished four types of cells with different characteristic morphological features.…”
Section: Discussionmentioning
confidence: 76%
“…The lipid composition of the HG has been positively stained with Sudan black in rabbits (Kasama et al 1973;Rock and Snyder 1975;Rock et al 1976), rats (Murawski and Jost 1974;Zackor and Murawski 1976), golden hamster (Lopez et al 1993), mice (Watanabe 1980), and guinea pigs (Yamazaki et al 1981). However, Sudan black revealed no lipid composition of the HG in ducks (Ballantyne and Fourman 1967), chickens, turkeys, pheasants, and the cardinal (Paule 1957;Sakai 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Inasmuch as the biochemical routes of porphyrin synthesis in the rodent Harderian gland have been known for a long time (Kennedy 1970: Margolis, 1971) pet the mechanisms of secretion are still obscure and controversial. Thus, most researchers believe that porphyrins are exclusively accumulated in the lipid droplets and secreted by merocrine mechanisms (Brownscheidle and Niewenhuis, 1978;Strum and Shear, 1982;Lopez et al, 1993) although, none of the former reports identified the porphyrins from an ultrastructural point of view. However, Carriere (1985) described protoporphyrin IX crystals in the secretory cells of the rat Harderian gland, suggesting holocrine mechanisms due to cell death.…”
Section: Al V-s Mrna Levelsmentioning
confidence: 99%
“…However, these pigments were not identified in the cytoplasm of the secretory cell types and the ultrastructural details related to its generation remain an enigma. Some investigators have suggested that porphyrins are secreted together with the lipid droplets but conclusive evidence has not been reported (Brownscheidle and Niewenhuis, 1978;Lopez et al, 1993). In the rat Harderian gland, straight and curved trilaminar profiles identical to those found in the luminal masses of porphyrin pigment were observed in the cytosol, concluding that some of the free porphyrins may be released through holocrine mechanisms (Carriere, 1985).…”
mentioning
confidence: 99%